2013
DOI: 10.1007/s10637-013-9949-4
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-human dose-escalation study of ME-143, a second generation NADH oxidase inhibitor, in patients with advanced solid tumors

Abstract: SummaryBackground ME-143, a second-generation tumor-specific NADH oxidase inhibitor, is broadly active against human cancers in vitro and in vivo. This first-in-human dose-escalation study evaluated the dose-limiting toxicities (DLTs), pharmacokinetics, safety, tolerability, and preliminary anti-tumor activity of ME-143 in patients with advanced solid tumors. Methods Patients with advanced solid tumors were treated in a 3 + 3 escalation design. ME-143 was administered via intravenous infusion on days 1, 8, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…ME‐344 has a mechanism of action that is distinct from ME‐143, a related drug candidate currently under clinical evaluation . The overall safety profile of ME‐344 was similar to that described in the first‐in‐human trial of ME‐143, with the exception of the AE of peripheral neuropathy observed in the current trial.…”
Section: Discussionsupporting
confidence: 61%
“…ME‐344 has a mechanism of action that is distinct from ME‐143, a related drug candidate currently under clinical evaluation . The overall safety profile of ME‐344 was similar to that described in the first‐in‐human trial of ME‐143, with the exception of the AE of peripheral neuropathy observed in the current trial.…”
Section: Discussionsupporting
confidence: 61%
“…The accumulating knowledge on the mechanism of action of flavonoids, as briefly summarised here, together with information on different structure--activity relationships has led to promising new research rationales. In fact, there are several examples of promising novel flavonoids with improved properties that are currently at different stages of development towards their potential application in the treatment of ovarian and breast cancer [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, proapoptotic effects may result from interference with mitochondrial functions (Kamsteeg et al, 2003) and interference with plasma membrane electron transport and/or cell surface thiol: disulfide exchange reactions (Morre and Morre, 2003;Herst et al, 2007). Downstream of such events, phenoxodiol derivatives can activate caspase-dependent and independent apoptotic pathways, perhaps through protein kinase B (Akt) signaling events (Wang et al, 2011;Pant et al, 2014). Related isoflavones alter mitochondrial membrane potential, deplete ATP, reduce steady-state levels of cytochrome c oxidase (complex IV of electron transport chain), and might eventually inhibit mammalian target of rapamycin (mTOR) activity .…”
Section: Introductionmentioning
confidence: 99%